The predictors of spiritual dryness among Iranian cancer patients during the COVID-19 pandemic - Farahani, Azam Shirinabadi; Kerdar, Sara Hamideh; Ashrafizadeh, Hadis; Büssing, Arndt; Mehrnoush, Nasrin; Akbari, Mohammad Esmaeil; Karami, Maryam; Tajalli, Salehe; Mojen, Leila Khanali; Rassouli, Maryam (Frontiers in Psychology, 2023)
Background:Spiritual struggles affect the wellbeing of religious people. Among them are strugglers with God which is perceived as non-responsive and distant. These perceptions were so far analyzed predominantly in Western societies with Christian background, but not in Muslims from Iran. The aim of this study was to determine the predictors of spiritual dryness among cancer patients in Iran during the COVID-19 pandemic. Methods: Descriptive study with standardized questionnaires (i.e., Spiritual Dryness Scale, WHO-5, BMLSS-10, Awe/Gratitude Scale) among 490 cancer patients (mean age 49.50 ± 14.92 years) referring to the selected educational hospitals in Tehran, who were selected through convenience sampling and based on the inclusion criteria, enrolled between December 2020 to May 2021.Data analysis was done using SPSS software version 26 and the statistical methods including calculating the mean and the standard deviation, correlation coefficients, as well as regression analysis. Results:The overall experience of spiritual dryness was perceived regularly in 10.2% of Iranian cancer patients, sometimes in 22.9%, rarely in 22.9%, and never in 43.3%. The mean±SD was 25.66± 5.04, and the scores ranged from 10 to 55. A higher score means greater spiritual dryness. The strongest predictors of spiritual dryness were praying activities Furthermore, the perception of burden due to the pandemic was positively correlated with spiritual dryness. Moreover, each 1 unit increase in its score changed the spiritual dryness score by 0.2 units. The regression of spirituality related indicators, demographic-clinical variables, and health-related behaviors accounted for 21%, 6%, and 4% of the total SDS variance, respectively. These findings show that with an increase in praying, performing daily prayers, and the indicators related to spirituality, spiritual dryness will decrease. Most patients were able to cope with these phases often or even regularly, while 31.1% were never or rarely only able to cope. Conclusions:In times of crisis, cancer patients’ faith and confidence in God could be challenged. It is not the disease itself which seems to be associated with this form of crisis, but their religious practices. It is necessary to support patients during their struggle, especially as spirituality is one of the best approaches to cope with the disease.